Typicality of food in five coastal markets in Chile - Saavedra-Gallo, Gonzalo (2025)
This article explores the construction of the concept of typical seafood products in five localized coastal markets (LCM) in Chile. The literature review shows that studies on typicality in these markets are scarce, so this paper contributes to the debate on the importance of typical foods in these organizations. The methodology used was ethnographic, complemented with questionnaires and interviews and documentary research. Among the results obtained, it was found that the typicality of marine products is constructed by key actors in the market – consumers, artisanal fishers, and merchants, who grant meanings and values to border-marine foods – that is, foods from the particular ecosystems on the edge of coastal territories and the coastal zone. It is concluded that these meanings are related to the natural resources, the abundance of the product, the territorial roots, the frequency of consumption, the symbols, and the recognition of the work of those who dedicate themselves to fishing. The study opens a line of research on artisanal fishing and coastal markets from the approach of localized agri-food systems and may be useful for the design of policies aimed at such markets.